Resilience Planning: Forging a New Planning Paradigm - Newman, Peter; Beatley, Tim (World Planning Schools Congress, 2011)
The environment has been a significant focus for planning education since the 1960’s. This paper traces the transition of environmental planning through the sustainability era to the emergence of a new and more accelerated transition that increasingly is termed resilience. It outlines the emerging characteristics of resilience and suggests they need to become part of a new paradigm in planning education – resilience planning.